Characterization of Irrigated and Rainfed Saline Vertisols of Bara Tract (Bharuch) of Gujarat - Kumar, Shrvan; Das, Amaresh; Chinchmalatpure, Anil R.; Prasad, Indivar (Annals of Arid Zone, 2023)
Four representative pedons (2-irrigated and 2-rainfed areas) were studied, interpreted and horizon-wise sampled as per standard procedure (Soil Survey Staff, 1995) to characterize the salt affected soils of Bara tract of district Bharuch, Gujarat. Soil samples were collected at horizon-wise differentiation to a depth up to 150 cm. In general, soil color was dark brown (10YR 4/3) or very dark grayish brown (10YR 3/2) or very dark brown (10YR 2/2) with clayey texture having structure varying from medium moderate sub-angular to coarse strong angular blocky. Pedons were classified up to a family level where temperature regime is Hyperthermic and texture is fine with Montmorillonite. Classification up to sub group level were as follows: pedon 1- Entic Chromusterts, pedon 2-(calcareous) Entic Chromusterts, pedon 3 and 4 (calcareous), Udorthentic Chromusterts. Soil pH, ECe, SOC, CaCO3, CEC and ESP of irrigated pedons varied respectively from 7.78 to 8.57, 0.75 to 12.50 dS m-1, 2.2 to 7.2 g kg-1, 2.6 to 196.4 g kg-1, 39.0 to 52.3 cmol (p+) kg-1 and 3.3 to 27.1, while the corresponding values in rainfed pedons were 8.29 to 8.85, 0.75 to 8.90 dS m-1, 2.6 to 5.7 g kg-1, 2.6 to 272.1 g kg-1, 36.9 to 50.7 cmol (p+) kg-1 and 2.8 to 18.1, respectively. Salinity/or Sodicity and calcareousness was occurred at sub-surface layers in irrigated saline Vertisols. Soil saturation extract revealed the dominance of Na+ cation followed by Mg2+, Ca2+ and K+, while in anions the trend was Cl- >SO4 2- HCO3 - +CO3 2-. SAR values were higher in irrigated conditions as compared to rainfed. The higher ESP was found due to regular irrigation of canal/ borewell/tubewell water etc. which ultimately induced the sodification process in the surface as well as sub-soils, while higher ESP was found in lower soil depths and tends to be sodic. The study thus advocates that continuing the present anthropogenic activities might render the soils unsuitable for agricultural production in the future. Further, looking at the sodicity/salinity build up, physical nature of Vertisols as well as groundwater quality constraints, suggests that it would be prudent to encourage irrigated/ or rainfed agriculture in the areas under improved management practices to sustainable crop production and improve the soil health.